SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/134695-ms
|View full text |Cite
|
Sign up to set email alerts
|

Key Criteria for a Successful Microseismic Project

Abstract: As microseismic monitoring expands, a wide variety of monitoring configurations have evolved including vertical, horizontal and deviated observation wells as well as surface and near-surface monitoring. All monitoring configurations have a common data quality indicator: signal-to-noise ratio (SNR) such that the higher the SNR the more accurate and confident the results. The key criteria for a successful microseismic project therefore primarily involve maximizing SNR. Data acquisition can be designed to optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…SRV is usually calculated using the dimensions of the 3D seismic cloud that is commonly associated with both measurement uncertainty and tendency towards over SRV estimations [37]. Through early evaluations of the relationship between the measurement uncertainty and the volume of microseismic cloud, Reference [38] indicated that larger source location uncertainty is associated with the larger the microseismic cloud volume with a tendency to overestimate the underlying deforming volume. The tendency towards SRV overestimated develops due to the microseismicity induced by stresses of hydraulic treatment acting on pre-existing structures, which is usually not represented in geomechanical models [6].…”
Section: Discussionmentioning
confidence: 99%
“…SRV is usually calculated using the dimensions of the 3D seismic cloud that is commonly associated with both measurement uncertainty and tendency towards over SRV estimations [37]. Through early evaluations of the relationship between the measurement uncertainty and the volume of microseismic cloud, Reference [38] indicated that larger source location uncertainty is associated with the larger the microseismic cloud volume with a tendency to overestimate the underlying deforming volume. The tendency towards SRV overestimated develops due to the microseismicity induced by stresses of hydraulic treatment acting on pre-existing structures, which is usually not represented in geomechanical models [6].…”
Section: Discussionmentioning
confidence: 99%
“…Velocity calibration is an indispensable data processing step in microseismic monitoring, which obtains reliable initial models for microseismic data analysis (Cipolla et al 2012;Maxwell et al 2010). Various methods have been applied to this problem (Pei et al 2009;Warpinski et al 2005;Warpinski and Du 2013).…”
Section: Numerical Examples Of the Pso Algorithm Applied To Velocity mentioning
confidence: 99%
“…The ability of this SNR filter to high grade the event data set has been described previously (e.g. Maxwell et al, 2010). An SNR filter can be extended to consider additional quality control attributes (Maxwell et al, 2007) such as confidence level defined as a score between 0 (min) and 5 (max) for contributing factors of p-and s-wave SNR, arrival time residuals and hodogram consistency.…”
Section: Selecting Highest Quality Eventsmentioning
confidence: 99%